IDENTIFY STUDENT CHARACTER OF THE MILLENNIAL ERA AND ITS EFFECT ON LEARNING MOTIVATION AND COUNSELING TEACHER ROLE - Abdurrahman Abdurrahman; Tamrin Sikumbang; Suleman Suleman (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2019)
The results of this study are: 1) There isa very basic difference in the character of the millennial era with previous generations. 2) There areeffects of the student character of the millennial era on the motivation to learn both positively and negatively, but negative effects are found to be more dominant than the positive effect. 3)Performance role of teacher BK class VIII, State Junior High School 1 Perbaungan need to beimproved according to each individual by increasing the potential of academic, creativity and loyaltyin order to provide guidance and service to the learners So as to provide services and empower thepotential of learners in the learning process and to respond to the development of the developingmillennial character.